The substantive and dialogical dimensions of critical thinking in high school and university students - Remache Bunci, Manuel Gonzalo (2020)
Critical thinking is undoubtedly one of the fundamental pillars in the personal, social and academic development of the individual because it helps to process and build knowledge aware of the real world; In this study it is necessary to analyze and evaluate the students, as well as to determine the evolution and differences in the substantive and dialogical dimensions in high school students, second and seventh level of university students. On this basis, 375 students were investigated, with the quantitative approach, emphasized in the analysis of descriptive and comparative character in the beginning with the group data to the normality test of Shapiro Wilk (when dealing with discrete scores). The substantive writing dimension had a significance p = 0.05, so the Kolmogorv Smirnov test with Lilliefor correction was necessary, obtaining a significance p = 0.11, with which it can be said that all met the criterion of normality (p> 0.05). With respect to the research objectives, the mean value for each of the dimensions and categories was considered, in order to establish the hypothesis tests according to the ANOVA statistic and the Tukey test at a significance of 5%. From the results obtained it was determined that there are shortcomings in high school students and decrease as they go beyond the level of instruction.